The Effectiveness of One Visit Vital Pulpotomy in Primary Teeth - Henri Hartman (Universitas Kristen Maranatha, 2018)
Primary teeth caries is a common problem in pre-school children; commonly caused by highsugar consumption dan food impaction. Primary teeth caries in posterior region can cause painfulattack on child and needs root canal treatment with many treatment visits. We reported pulp therapyon 8 years old child with irreversible pulpitis 54, treated by one visit vital formocresol pulpotomy.Patient came with acute condition, pain on upper posterior area. Intra oral examination showedcaries on teeth 54 with pulp involved and caries dentin on 55. Vitality test (+), mobility (-), percussion(+), and no sign of soft tissue abnormality. Vital pulpotomy was chosen for 54 treatment, bleedingcontrol with formocresol, obturation with Zinc Oxide Eugenol (ZOE), and finally restoration withstainless steel crown, all treatment was done in one visit. Four month evaluation showed no complaintreported. We concluded one visit pulpotomy for pulp therapy showed optimum result in primary toothand reduce the necessity of multiple treatment visits.Keywords: formocresol, primary teeth, stainless steel crown, vital pulpotomy